Bioactivity of Piper extracts on Tuta absoluta (Lepidoptera: Gelechiidae) in tomato - Brito, Elaine Ferrari de [UNESP]; Lopes Baldin, Edson Luiz [UNESP]; Macedo Silva, Roney de Carvalho [UNESP]; Ribeiro, Leandro do Prado; Vendramim, Jose Djair (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate the bioactivity of ethanolic leaf extracts from four species of the genus Piper against the tomato leafminer Tuta absoluta (Lepidoptera: Gelechiidae) under laboratory conditions. The evaluated species were: P. amalago var. medium, P. glabratum, P. mikanianum, and P. mollicomum. In the initial screening assay (extract concentration of 2,000 mg L-1), all tested extracts caused significant larval mortality, particularly the extract of P. amalago var. medium; however, no extracts reduced the weight of the surviving larvae. The extract from P. amalago var. medium at the concentration of 1,011 mg L-1 caused a significant lengthening of the larval and pupal stages. The ethanolic leaf extract of P. amalago var. medium is promising for the control of T. absoluta larvae in tomato, since it exhibits acute toxicity toward these caterpillars at the concentration of 2,000 mg L-1 and affects the insect's development by reducing its survival and lengthening the larval and pupal stages.

O objetivo deste trabalho foi avaliar a bioatividade de extratos etanólicos de folhas de quatro espécies do gênero Piper sobre a traça-do-tomateiro Tuta absoluta (Lepidoptera: Gelechiidae), em condições de laboratório. As espécies avaliadas foram: P. amalago var. medium, P. glabratum, P. mikanianum e P. mollicomum. Na triagem inicial (concentração do extrato de 2.000 mg L-1), todos os extratos testados causaram significativa mortalidade larval, principalmente o extrato de P. amalago var. medium; entretanto, nenhum extrato ocasionou redução do peso das lagartas sobreviventes. O extrato de P. amalago var. medium na concentração de 1.011 mg L-1 promoveu alongamento significativo da fase larval e pupal. O extrato etanólico de folhas de P. amalago var. medium é promissor no controle de lagartas de T. absoluta em tomateiro, pois exibe toxicidade aguda a lagartas na concentração de 2.000 mg L-1 e afeta o desenvolvimento do inseto, ao reduzir a sua sobrevivência e alongar as fases larval e pupal.
Bioatividade de extratos de Piper sobre Tuta absoluta (Lepidoptera: Gelechiidae) em tomateiro
Keywords: Piper amalago var. medium; Botanical extracts; Piperamides; Tomato leafminer; Piper amalago var. medium; Extratos botânicos; Piperamidas; Traça-do-tomateiro